The Effect of an Integrated Think Pair Share (TPS) Learning Model Based on Balinese Local Wisdom on Fifth-Grade Elementary Students’ Science Literacy and Learning Outcomes - Pande Luh Putu Eka Heriyanti; I Gusti Ayu Tri Agustiana; Gde Wawan Sudatha (Jurnal Pendidikan Multikultural Indonesia, 2025)
The low level of scientific literacy in Indonesia in the context of international comparisons remains a concern. One possible cause of this decline can be observed in the curriculum and educational aspects, which need further evaluation to improve the quality of science learning in the country. This study aims to explore the effect of the Think Pair Share (TPS) learning model integrated with Balinese local wisdom on scientific literacy and learning outcomes of fifth-grade elementary school students. This research employed a quasi-experimental design using a Posttest-Only Control Group Design. The population consisted of all fifth-grade elementary school students, with samples selected through intact group random sampling. The sample was divided into two groups: an experimental group (TPS integrated with Balinese local wisdom) and a control group (conventional method). Data were collected through achievement tests and a scientific literacy questionnaire. Data analysis was conducted using the Multivariate Analysis of Variance (MANOVA) test with a significance level of 5%. The results showed a significant difference between the two groups in terms of scientific literacy and learning outcomes, with an F value of 232.004 and a significance level of 0.000 (<0.05). These findings confirm that TPS integrated with Balinese local wisdom positively influences students’ scientific literacy and learning outcomes by promoting active participation, better conceptual understanding, and higher motivation in learning. The integration of Balinese local wisdom also helps students connect knowledge with cultural values, thereby enhancing their understanding of the learning material.